CURRENT CONFLICT OF IDENTITIES ON THE UKRAINIAN-RUSSIAN BORDERLAND (peer-review on the collective monograph: Vermenych Ya. V. The Ukrainian-Russian Borderland in the Space of Identities Conflict in History and Modernity / Editor in-Chief V.A. Smolii. Kyiv: Institute of History of Ukraine, NAS of Ukraine, 2024. 331 p.) - HRYTSENKO , Halyna; TALALAY, Yuliya (EAST EUROPEAN HISTORICAL BULLETIN, 2025)
peer-review on the collective monograph: Vermenych Ya. V. The Ukrainian-Russian Borderland in the Space of Identities Conflict in History and Modernity / Editor in-Chief V.A. Smolii. Kyiv: Institute of History of Ukraine, NAS of Ukraine, 2024. 331 p.